"Doing the Right Thing": Family Caregivers Managing Medical and Nursing Tasks in the Postacute Home Health Care Setting. (December 2021) - Chase, Jo-Ana D.; Russell, David; Kaplan, Daniel B.; Bueno, Michael V.; Khiewchaum, Rungnapha; Feldman, Penny H.
Family caregivers often manage complex medical and nursing tasks (MNTs) for older adults transitioning from hospital to home. To explore caregivers' experiences managing MNTs in the postacute home health care (HHC) setting, we interviewed by phone 20 caregivers of older adults who received HHC following a hospitalization. Interviews were recorded, transcribed, and analyzed using directed content analysis. Caregivers highlighted the technical complexity and emotional impact of performing MNTs, as well as social (e.g., family, friends) and environmental (e.g., neighborhood, housing) resources they leveraged to meet the older adults' care needs. Caregivers also identified challenges coordinating care and services within HHC and the larger health care system. Caregiver engagement in the postacute HHC setting should incorporate tailored training and support, assessments of socioenvironmental context and resources, and facilitated navigation of the health care system. Future research should elucidate factors associated with successful collaborative relationships among HHC providers, older adults, and their caregivers in the postacute HHC setting.